Lignin Chemistry, Structure, and Application - Sand, Arpit; Tuteja, Jaya (IntechOpen, 2023)
Lignin, found in the cell walls of trees and plants, is the second-most naturally abundant biopolymer. It is composed of alkyl-aromatic polymer units. This book describes the composition and structure of lignin, strategies for its chemical modification, and studies of biopolymer lignin. It also discusses the synthesis and characterization of lignin, methods for degradation, applications in various materials, and prospects for further development. Other topics covered include the role of lignin in thermosetting and thermoplastic materials and its technical and economic potential for generating green biofuel as an energy source for industrial plants and in the manufacture of fine chemicals.